Early diagnosis of iniencephaly: a case report with review of literature - Singh, Alpana; Mundhra, Rajlaxmi; Manchandra, Smita; Radhakrishnan, Gita; Meena, Pragati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Iniencephaly is a rare and fatal neural tube defect characterized by retroflexion of fetal head with absent neck due to spinal defects. Herein, we describe a case of iniencephaly with a brief review of literature.